Case report Additional openings of the coronary sinus and associated anomalies - Das, Srijit; Paul, Shipra (Archives of Medical Science, 2006)
The coronary sinus normally opens into the right atrium through a single orifice. Past research studies have described various anomalies of the coronary sinus but there are fewer reports on multiple orifices of the coronary sinus. The present study reports two additional orifices of the coronary sinus opening into the right atrium and associated anomalous vessels. The presence of multiple orifices may be clinically important during any catheterization and cardiac surgeries and for proper interpretation of angiographic studies.